Biodiversity and community structure of Ban Non- Hin Phueng community forest, Thailand - Hasin, Sasitorn (Asian Science and Technology Innovation Journal, 2025)
Community forests play a critical role in conserving biodiversity while supporting local livelihoods, particularly in tropical regions where forest-dependent communities remain prevalent. This study investigated the biodiversity of vascular plants, mammals, edible insects, and edible mushrooms in Ban Non-Hin Phueng Community Forest, Prachinburi Province, Thailand, to provide a scientific basis for sustainable conservation and resource-use planning. Biodiversity data were collected through systematic ecological surveys and participatory fieldwork with local community members. Resource utilization patterns were classified into four main categories: (1) food resources derived from plants, wildlife, edible insects, and wild mushrooms; (2) medicinal plant use; (3) plant materials for housing construction and maintenance; and (4) commercial utilization of biological resources. The results reveal that the Ban Non-Hin Phueng Community Forest constitutes a socio-ecological system characterized by mutual benefits between forest ecosystems and local communities. Forest resources contribute directly to household food security and income generation, while strong community participation enhances forest protection and regeneration. The forest exhibits clear signs of ecological recovery following historical logging, with high regeneration potential reflected by the abundance of saplings and seedlings relative to mature trees. These findings highlight the importance of integrating biodiversity conservation, traditional ecological knowledge, and community-based governance to achieve long-term sustainability in community forest management.